IMPLEMENTATION OF INTERNSHIP DATA MANAGEMENT APPLICATION WITH PROTOTYPE METHOD AND USER ACCEPTANCE TEST METHOD - Laura Mahendratta Tjahjono; Gladys Greselda Gosal (Informatika, Universitas Jenderal Soedirman, 2023)
Universities generally have programs that offer students internship opportunities in departments within the university. In several universities especially Universitas Ciputra, internships in departments within these universities are mandatory activities for scholarship recipient students. This internship activity involves many parties, including students implementing internships, departments that provide internship vacancies and also student bureaus that monitor the implementation of internships. The obstacle faced in this activity is the difficulty of fulfilling internship vacancies with students who have interests, abilities and profiles that match the requirements of internship vacancies. The student bureau also has difficulty monitoring the progress of the implementation of internship activities in the field. The purpose of this research is to provide a solution to the problems faced in this internship in the form of a website application developed using the Prototype Model method using the Laravel framework and tested using the User Acceptance Test (UAT) method. The result of this research is a website prototype that can be used. The results of the UAT test show that the application made can help solve problems in this internship activity with a user satisfaction level of up to 96%.